Spontaneous hemorrhage of an adrenal myelolipoma treated with transarterial embolization: A case report - Kabeel, Khalid (Radiol Case Rep, 2020)
Adrenal myelolipoma is a benign tumor of the adrenal cortex composed predominantly of fat and hematopoietic tissue. These lesions are usually asymptomatic, and most often incidentally detected on imaging. Uncommonly, they present with retroperitoneal hemorrhage, and these have been traditionally treated with emergent surgery. Although, transarterial embolization has been effectively and safely used in patients presenting with active hemorrhage from acute traumatic and nontraumatic causes, literature specifically pertaining to adrenal artery embolization is scant, perhaps due to smaller size and variability of adrenal arteries. With recent advances in endovascular techniques and imaging, there are emerging case reports and series of adrenal artery embolization in acute and nonacute settings. We report a case of spontaneous hemorrhage within an adrenal myelolipoma in a 43-year-old male patient, successfully treated with transarterial embolization, thereby avoiding major surgery. Our report adds to the growing body of literature pertaining to adrenal artery embolization.